Sources: the UFMG archives of the history of psychology in Brazil - Campos, Regina Helena de Freitas (History of Psychology, 2010)
This article discusses the Federal University of Minas Gerais (UFMG) Archives of the history of psychology in Brazil. The Archives were originally established in 1997, in the Helena Antipoff Room at the Central Library of the UFMG. The team responsible for today’s archive operations has grown to include psychology and education archival specialists, as well as personnel trained in conservation and restoration techniques and consultants who provide advice on the organization of the material. As psychology in Brazil is profoundly related to the history of education, above all to the history of educational thinking and the systems of teaching, the collections also constitute material of interest to education historians. Thus, in institutional terms, the UFMG Archives of the History of Psychology in Brazil are connected both to the postgraduate programs in psychology, “History of Psychology and Sociocultural Context,” and education, “Psychology, Psychoanalysis and Education,” at the UFMG.